MINERALOGICAL-GEOCHEMICAL FEATURES OF ZIRCON FROM THE KUMIR GRANITIC STOCK, GORNY ALTAI - A.I. Gusev (Минералогия)
Data on U-Pb age and composition of zircon from the Kumir granitic stock (Gorny Altai) and related greisens are presented for the first time. The magmatic, metamictic and pneumatolytic-hydrothermal zircons exhibit specific changes in main and trace elements with an increasing content of the high-field strength elemetns (U, Nb, Sc, REE) and decreasing Eu/Eu* and Ce/Ce* ratios. Depending on the composition and activity of volatiles in fluids and O fugacity, the REE contents and their ratios varied that is reflected on the tetrad effect of REE fractionation of М- and W- types.